Effect of Malaria and Malaria Chemoprevention Regimens in Pregnancy and Childhood on Neurodevelopmental and Behavioral Outcomes in Children at 12, 24, and 36 Months: A Randomized Clinical Trial. (11th October 2022) - Bangirana, Paul; Conroy, Andrea L; Opoka, Robert O; Semrud-Clikeman, Margaret; Jang, Jeong H; Apayi, Claire; Kakuru, Abel; Muhindo, Mary K; Georgieff, Michael K; Dorsey, Grant M; Kamya, Moses R; Havlir, Diane; et al.
Abstract: Background: Malaria in pregnancy has been associated with worse cognitive outcomes in children, but its association with behavioral outcomes and the effectiveness of malaria chemoprevention on child neurodevelopment are not well characterized. Methods: To determine if more effective malaria chemoprevention in mothers and their children results in better neurodevelopment, 305 pregnant women were randomly assigned to 3 doses of sulfadoxine-pyrimethamine, 3 doses of dihydroartemisinin-piperaquine (DP), or monthly DP during pregnancy, and their 293 children were assigned to DP every 3 months or monthly DP from 2 to 24 months of age. Cognition, language, and motor function were assessed at 12, 24. and 36 months of age, and attention, memory, behavior, and executive function were assessed at 24 and 36 months of age. Results: Children of mothers with versus without malaria in pregnancy had worse scores on cognitive, behavioral, and executive function outcomes at 24 months. Clinical malaria in children within the first 12 months was similarly associated with poorer scores in behavior and executive function at 24 months, language at 24 and 36 months, and motor function scores at 36 months. However, more effective malaria chemoprevention in the mothers and children was not associated with better outcomes. Conclusions: Malaria in pregnancy was associated with worse cognitive, behavioral, and executive function scores in affected children, but more effective malaria chemoprevention measures did not result in better outcomes. Malaria chemoprevention prior to and early in gestation and with even higher efficacy in mothers and children may be required to prevent neurodevelopmental impairment in children. Clinical Trials Registration. NCT02557425. Abstract : Malaria in pregnancy and early childhood was associated with worse neurodevelopmental outcomes in children, but more effective maternal and child malaria chemoprevention regimens did not result in better neurodevelopmental outcomes.